Holistic Management of 61 Year Old Mr. J with Diabetes Mellitus and Vertigo through A Medical Approach Family - Hasna, Afina; Utama, Winda Trijayanti (Jurnal Penelitian Perawat Profesional, 2025)
Chronic diseases such as diabetes mellitus and vertigo are common in elderly patients and often coexist, impacting their quality of life and daily functioning. The family medicine approach emphasizes holistic care that is patient-centered, family-focused, and community-oriented, which is essential for managing multiple chronic conditions effectively. This case report describes the holistic management of a 61-year-old male patient, Mr. J, diagnosed with type 2 diabetes mellitus and recurrent vertigo. Management strategies involved pharmacological treatment, lifestyle modification, dietary counseling, education about medication adherence, family involvement, and home visit follow-ups. After intervention, Mr. J showed improved blood glucose control, reduced frequency of vertigo episodes, and better medication adherence. His understanding of the disease and self-management skills also improved, supported by enhanced family involvement and environmental modifications. The patient's quality of life and daily activity levels increased significantly. A holistic approach based on family medicine principles can significantly improve clinical outcomes and quality of life in elderly patients with comorbid chronic diseases such as diabetes and vertigo. Integrating family support and individualized education plays a crucial role in sustaining long-term health improvements.